On the existence of uniformly consistent estimates - Yatracos, Yannis G. (My University, 1985)
Let M be a family of probability measures on (X, A) and U the uniform structure defined by vicinities of the form (formule presented) where Pn is the product measure on (formula presented), where (formula presented) We consider the case where the space of measures M is Lt separable and relate the existence of uniformly consistent estimates for φ* (P) with uniform continuity of φ* and L1-total boundedness of M. © 1985 American Mathematical Society.
Keywords: Lx total boundedness of the space of measures; Minimum distance estimation; Uniformly consistent estimation of a functional of a measure